Peptide:MHCII Tetramer‐Based Cell Enrichment for the Study of Epitope‐Specific CD4+ T Cells. (29th April 2019) - Kotov, Dmitri I.; Jenkins, Marc K.
Abstract: Epitope‐specific CD4 + T cells can be labeled in complex cell mixtures from secondary lymphoid organs with fluorophore‐labeled peptide:major histocompatibility complex class II (p:MHCII) tetramers and then detected by flow cytometry. Magnetic enrichment of tetramer‐bound cells before flow cytometry increases the sensitivity of detection to the point where epitope‐specific cells can be studied even when very rare at early and late times after the host has been exposed to the epitope. This method is very useful for studying polyclonal epitope‐specific CD4 + T cells under physiological conditions. © 2019 by John Wiley & Sons, Inc.